FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING: STUDI EMPIRIS PERUSAHAAN MANUFAKTUR - Manalu, Agatha Avhia Dorothea; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study was used to find out whether there is a significant influence of the independent variables namely Profitability, Financial Leverage, Company Age, Company Size, and Underwriter's Reputation on the dependent variable, namely the level of Underpricing in this study using manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) and also already conducted an IPO in the 2017-2020 period. In this study, a purposive sampling method was used and the research objects used in this study were 35 samples. From this research, the results obtained are that profitability and the underwriter's reputation do not affect the level of underpricing, for financial leverage according to the test results, namely a positive effect on the level of underpricing, while for the age of the company, the size of the company based on the test results is negative on the level of underpricing.